Explorative Study of Gen-Z Muslim Teenagers, Social Media, and Spiritual without Form: Study of Mosque Teenagers in Pancor Village - Dina Rosa Kusumayanti (Lembaga Bale Literasi, 2025)
The article explores the spiritual perspective of Muslims in Generation Z as it relates to Pancor City's Mosque Youth. For the Muslim Gen-Z generation, spiritual matters are significant since they are thought to have the potential to create a more directed guidance. Research concerns regarding the identities of Gen- Z Muslims, their spiritual sources, and their understanding of spiritual forms are posed by this study. The research methodology employs a qualitative approach that uses descriptive analysis to describe a phenomenon. This kind of research is exploratory, meaning it looks for new hypotheses or ways to expand on existing ones. The main data source is Pancor City's Mosque Youth. gathering information through focus groups, documentation, and observation. After that, data analysis was completed using reduction to condense the information discovered to be categorized and shown thorough examination. According to this study, Gen-Z Muslims are a group of young Muslims who are still in school. They are influenced by social media and learn about religion through involvement in religious groups and recitation. More reliable sources of spiritual wisdom are still required. Ultimately, the study validates that the spirituality of Gen -Z Muslims lacks a defined form due to a lack of authoritative resources.